RESPON CYLINDROCLADIUM SP. TERHADAP FUNGISIDA BERBAHAN AKTIF METIRAM SECARA IN VITRO - Sri Martina Suseno; Edy Batara Mulya Siregar; Ridwanti Batubara (Peronema Forestry Science Journal, 2016)
Cylindrocladium sp. is a pathogen cause disease that attack eucalyptus and  it  was the highest type of disease that attack eucalyptus in toba pulp lestari. Fungicide was used to eradicate and prevent the growth of pathogens. One of the fungicide which  used was systemic fungicide with active substance metiram 70 %. The purpose of this study was to measure the area, diameter, density of the spore ,and to characterize the hyphae form of Cylindrocladium sp after being treated metiram 70 % in vitro in different concentrations. Sample that used taken from cylindrocladium collection from previous research. The result of this study showed that the most efective concentration of fungicide treatment in inhibiting growth and development area of cylindocladium sp was treatment 2,0 mg/ml. In observation of spore density and hyphae structures of cylindrocladium sp, the fungicide that given was able to give tangible effect but in observation of relative inhibiton, concentration of fungicide gave intangible effect in providing inhibition to pathogen of cylindrocladium sp.Keywords: eucalyptus, cylindrocladium sp, fungicide, metiram, in vitro